Nutritional habits providing optimal calcium and vitamin D3 supply - Grygiel-Górniak, Bogna; Pawlak-Buś, Katarzyna; Leszczyński, Piotr (Menopause Review/Przegląd Menopauzalny, 2012)
A well-balanced diet is important in prevention and treatment of osteoporosis. Among nutritional factors influencing bone health not only a proper intake of calcium and vitamin D, but also the supply of protein, magnesium, potassium, zinc, copper, vitamin K, vitamin B 6 and ascorbic acid is important. Assimilability of calcium from the diet ranges from 10% to 40% and depends on chemical molecule’s solubility and the composition of the diet. The factors increasing calcium absorption are lactose, inulin, selected fructooligosaccharides and casein phosphopeptides, lysine and arginine. The presence of caffeine, phytins, oxalic derivates, non-soluble dietary fibre fractions and excess intake of fat, phosphorus, alcohol and sodium chloride decrease calcium bioavailability and assimilability. Dietary education and modification of nutritional habits in the group of patients with osteoporosis are important factors preventing future development of this disease.